Investigation of Storm Tides Induced by Super Typhoon in Macro-Tidal Hangzhou Bay - Li, Li; Li, Zixuan; He, Zhiguo; Yu, Zhuzhu; Ren, Yihan (Frontiers in Marine Science, 2022)
Typhoon-induced storm tides can cause serious coastal disasters and considerable economic losses. Understanding the mechanisms controlling storm surges helps the prevention of coastal disasters. Hangzhou Bay (HZB), a typical macro-tidal estuary, is located on the east coast of China, where typhoons frequently occur. The funnel-shaped topography makes this macro-tidal bay even more sensitive to storm tides. Super Typhoon Chan-hom was used as an example to study the characteristics and dynamic mechanisms of storm surges using a well-validated numerical model. The model considers the two-way coupling of waves and tides. The wind strength for the model was reconstructed using multi-source wind data and was refined by considering different rotating and moving wind fields. The Holland–Miyazaki model was used to reconstruct the local wind-field data with a good performance. The model results show that the total water level of HZB during typhoon Chan-hom was mainly dominated by tides, and the storm surge was closely related to the wind field. Surface flow was mostly influenced by winds, followed by tides. The spatial and temporal distributions of the significant wave height were controlled by the wind and local terrain. Wind stress was the largest contributor to storm surges (91%), followed by the pressure effect (15%) and the wave effect (5%). Both wind and wave-induced surges occurred during low slack waters. The tide-surge interaction changes (enhance or suppress) the surge by approximately 0.5 m during the typhoon, comprising approximately 50% of the total surge. Tides interacted with surges through various mechanisms, from the bay mouth (local acceleration and friction) to the bay head (friction and advection). The Coriolis force had a relatively minor effect. The findings of this study provide useful information for studies on sediment dynamics and coastal structures under extreme weather conditions.